Introduction of the Hezar International Gravity Formula - Hassanpour, Mehdi; Rezaie, Mohammad Reza; Khezripour, Saeedeh; Faruque, Mohammad Rashed Iqbal; Khandaker, Mayeen Uddin (Frontiers in Physics, 2022)
The National Cartographic Center of Iran measured the differences in gravity between the Hezar summit and peak of Mount Damavand using a CG-5 gravity meter. The gravity recorded at the Hezar summit (4,499.416 m) was 213 mGal (0.00213 m/s2) lower than the reading recorded at the peak of Mount Damavand (5,605.730 m). Recently, the exact value of gravity at the Hezar summit and peak of Damavand mount have been measured. This study attempts to modify the conventional version of Hezar International Gravity Formula (HIGF) to calculate the experimental gravity in the Earth’s summits and land surfaces. Apart from describing the 213 mGal difference in gravity between Hezar summit and peak of Mount Damavand, HIGF is also in agreement with practical gravity with distance from sea level and latitude (93% confidence level). The results indicated that the experimental HIGF as g =978,031.85 (1 + 0.0053024 sin2θ−0.000032309786 sin22θ)−0.27 h was in agreement with the practical gravity compared to the 1984 International Gravitational Formula (IGF84).